A metamaterial with applications in broad band antennas used in radio astronomy and satellite communications. (1st June 2022) - De Miguel, J.; Franceschet, C.; Realini, S.; Fuerte-Rodríguez, P.
Abstract: Electromagnetic metamaterials at microwave frequencies are well established in industry and research. Recent work has shown how a specific kind of metallic metamaterial can contribute towards improving the performance of the feedhorn antennas used in radio astronomy and satellite telecommunications. In this article, we discuss an innovative type of meta-ring of remarkable manufacturability, able to improve the state of the art in these fields. A pioneering meta-horn antenna formed of meta-rings is then fabricated and characterized in the laboratory. It shows an excellent feature on an octave bandwidth, especially in terms of cross-polarization, a key figure of merit in both radio astronomy and telecommunications, and also side-lobe level, return-loss and gain.